Anti-emetic Action of the Brain-Penetrating New Ghrelin Agonist, HM01, Alone and in Combination With the 5-HT3 Antagonist, Palonosetron and With the NK1 Antagonist, Netupitant, Against Cisplatin- and Motion-Induced Emesis in Suncus murinus (House Musk Shrew) - Rudd, John A.; Chan, Sze W.; Ngan, Man P.; Tu, Longlong; Lu, Zengbing; Giuliano, Claudio; Lovati, Emanuela; Pietra, Claudio (Frontiers in Pharmacology, 2018)
Ghrelin has well-known activity to stimulate appetite and weight gain. Evidence suggests that ghrelin may also have useful effects in reducing chemotherapy-induced emesis via growth hormone secretagogue receptors (GHS-R1A) receptors in the brain. However, it is not known whether the stimulation of GHS-R1A has broad inhibitory anti-emetic effects. In the present studies, we used Suncus murinus to investigate the potential of the new and novel orally bioavailable brain-penetrating GHS-R1A mimetic, HM01 (1-[(1S)-1-(2,3-dichloro-4-methoxyphenyl)ethyl]-3-methyl-3-[(4R)-1-Methyl-3,3-dimethyl-4-piperidyl]urea), to reduce emesis induced by a variety of emetic challenges. HM01 (1 to 30 mg/kg, p.o.) antagonised emesis inducted by cisplatin (30 mg/kg, i.p.) and by motion (4 cm horizontal displacement, 1 Hz) but was ineffective against emesis induced by nicotine (5 mg/kg, s.c.) and copper sulphate (120 mg/kg by intragastric gavage). In other experiments, HM01 (3 mg/kg, p.o.) enhanced the anti-emetic control of a regimen of palonosetron (0.01 mg/kg, p.o.) alone and palonosetron (0.01 mg/kg p.o.) plus netupitant (1 mg/kg, p.o.). HM01 (10 mg/kg, p.o.) also had positive effects in increasing feeding and drinking in nicotine-treated animals, and it shortened the latency to drink in animals treated with cisplatin. These data indicate that brain-penetrating GHS-R1A agonists may have use alone and/or in combination with standard anti-emetic regimens for the treatment of chemotherapy-induced nausea and vomiting and motion sickness.